Socio-Economic Factors and Effects of Low Female Enrolments in Electrical Trade in Adamawa State - Zambwa, Joseph; Asukwo, Aniekan Elijah; James, Grace (Online Journal for TVET Practitioners, 2021)
This study determined the perceived socio-economic factors and effects of low enrolment of female students in Electrical Installation and Maintenance Works Trade in Government Technical Colleges on women empowerment in Adamawa State. Two specific objectives guided the present study. The population of the study consisted of 13 Electrical Installation and Maintenance Work Trade (EIMWT) teachers and 129 parents (either father or mother) of National Technical Certificate Two (NTCII) EIMWT students in three Government Technical Colleges of Adamawa State. The research subjects of the study comprised the entire population, thus no sampling was done. The instrument was validated by three experts and yielded a reliability co-efficient of 0.81. Mean was used in data analysis to answer the research questions. The findings of the study revealed an increasing number of technically unskilled female folks in Adamawa State as major perceived socio-economic effect. Other findings include gender inequality and regress in the fight to end poverty among the female folk in Adamawa State. The study recommended among others that Adamawa State Government in collaboration with corporate bodies should embark on an awareness campaign in order to enlighten parents and family members on the prospects of EIMWT especially to female gender.